REKAYASA NANO KOMPOSIT TITANIUM OSKIDA SEBAGAI KATALIS PEREDUKSI ZAT WARNA TEKSTIL - Iwan Susanto; Nugroho Eko Setijogiarto; Tia Rahmiati; Fachruddin Fachruddin; Arifia Ekayuliana; Jauhari Ali (Politeknik Negeri Jakarta, 2019)
The core shell structure of TiO2@SiO2@ferrite(Ni-Cu-Zn) as composite nanoparticles for magnetic photocatalyst were successfully prepared in this study. These particles were synthesized continually by the sol-gel method and they are tested for their performance using MB dye solution. The magnetic core particles used in the synthesis were (Ni-Cu-Zn) ferrite with size of 20-60 nm, while SiO2 and TiO2 layers were formed using tetraethoxysilane and tetrabutly titanate. Some characterizations and testinghavecarried out to investigate the crystal structure, magnetic properties, surface conditions and performance of these particles. The results show that the anatase crystal structure of TiO2 was obtained on the outer shell of the particle, while the magnetization value and surface area were achieved at 4.74 emu/g and 126,831 m2/g, respectively. The nanoparticles of composite size were obtained about 10 to 40 nm with the shell thickness up to 4 nm. The performance results of photodegradation was quite good for reducing MB dye up to 63.37%.